-2(5s-5)-10=-2(8s+10)-3

Simple and best practice solution for -2(5s-5)-10=-2(8s+10)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5s-5)-10=-2(8s+10)-3 equation:


-2(5s - 5)-10= -2 (8s + 10)-3

We simplify the equation to the form, which is simple to understand
-2(5s-5)-10=-2(8s+10)-3

Reorder the terms in parentheses
+(-10s+10)-10=-2*(8s+10)-3

Remove unnecessary parentheses
-10s+10-10=-2+*(+8s+10+)-3

Reorder the terms in parentheses
-10s+10-10=+(-16s-20)-3

Remove unnecessary parentheses
-10s+10-10=-16s-20-3

We move all terms containing s to the left and all other terms to the right.
-10s+16s=-20-3-10+10

We simplify left and right side of the equation.
+6s=-23

We divide both sides of the equation by 6 to get s.
s=-3.83333333333

See similar equations:

| 7(t+8.5)-5+4t= | | 5(r-4)=-10 | | Y=2(-2)+5 | | n/9=4 | | 7(t+8.5)-5+4= | | f*0.25=0.0625*2+2 | | 6x+9=39+3x | | 3y(y-2)-5y=-2(y+3) | | L+w=10+4(l-w) | | 25*x^2-30*x+9=81 | | 2x+5(3x-2)=8x+5 | | 0.62+p=62.87 | | b-12=-8 | | -12=a+6 | | .33c=-8 | | s-18=8 | | 1.5x-12=12 | | 6.5a+14=72.5 | | 10x^2-60-25x= | | 1.5(n-4.5)=12 | | 9w^2+24w+16= | | 4x+6=3x+8 | | 64s^2-121f^2= | | 6x-28x=12 | | e^3-7x=1554 | | 2n-4=9n+2 | | 9w^2+42wd+49d^2= | | x-8.9=-3.1 | | 2x^2+32x+12=0 | | r+28=18 | | M+35=172 | | -3(4m+1)+6m=4(2m-6) |

Equations solver categories